Immunomodulatory effects of inulin and its intestinal metabolites - Sheng, Wei; Ji, Guang; Zhang, Li (Frontiers in Immunology, 2023)
Dietary fiber" (DF) refers to a type of carbohydrate that cannot be digested fully. DF is not an essential nutrient, but it plays an important part in enhancing digestive capacity and maintaining intestinal health. Therefore, DF supplementation in the daily diet is highly recommended. Inulin is a soluble DF, and commonly added to foods. Recently, several studies have found that dietary supplementation of inulin can improve metabolic function and regulate intestinal immunity. Inulin is fermented in the colon by the gut microbiota and a series of metabolites is generated. Among these metabolites, short-chain fatty acids provide energy to intestinal epithelial cells and participate in regulating the differentiation of immune cells. Inulin and its intestinal metabolites contribute to host immunity. This review summarizes the effect of inulin and its metabolites on intestinal immunity, and the underlying mechanisms of inulin in preventing diseases such as type 2 diabetes mellitus, inflammatory bowel disease, chronic kidney disease, and certain cancer types.